2021
DOI: 10.21608/mid.2021.74461.1147
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virulence genetic profile and resistance patterns of clinical Klebsiella pneumoniae isolates: Classic versus hypermucoviscous phenotypes

Abstract: Background:Klebsiella pneumoniae (K. pneumoniae) is one of the most clinically important opportunistic pathogens involved in both community-(CAIs) and hospitalacquired infections (HAIs).The hypervirulent K.pneumoniae (hvKp) responsible for disseminated infections in healthy and immunosuppressed individuals has emerged with considerable ability to get antibiotic resistance as well. We aimed to characterize the virulence genetic profile and resistance phenotypes of the clinical K.pneumoniae isolates at Menoufia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is noteworthy that the sensitivity, specificity, and accuracy of string test for identifying hvKp, compared to PCR data of encoding genes, have been assessed in various previous studies. Elbrolosy (2021) study revealed that the sensitivity, specificity, and accuracy of string test are 95.2%, 79.3%, and 86%, respectively, with a positive predictive value of 76.9% and a negative predictive value of 95.8% [ 49 ]. In addition, Russo and Gulick (2019) demonstrated string test results to identify hvKp with a specificity of 89%, a sensitivity of 91%, and an accuracy of 90% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the sensitivity, specificity, and accuracy of string test for identifying hvKp, compared to PCR data of encoding genes, have been assessed in various previous studies. Elbrolosy (2021) study revealed that the sensitivity, specificity, and accuracy of string test are 95.2%, 79.3%, and 86%, respectively, with a positive predictive value of 76.9% and a negative predictive value of 95.8% [ 49 ]. In addition, Russo and Gulick (2019) demonstrated string test results to identify hvKp with a specificity of 89%, a sensitivity of 91%, and an accuracy of 90% [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result in concordance with Russo et al [29] who reported results near to ours as they stated that string test had 91% sensitivity, 89% specificity. But Elbrolosy et al and Tan et al [19,33] reported higher results regarding sensitivity 95.2%, 90.5% and lower regarding specificity 79.3%, 63.9% correspondingly.…”
Section: A C Bmentioning
confidence: 90%
“…In comparison to Seifi et al [18] who found that most of K. pneumoniae were isolated from urine samples. Another study that performed in Egypt by Elbrolosy et al [19] who reported the highest rate of K. pneumoniae was isolated from blood samples followed by respiratory secretions.…”
Section: A C Bmentioning
confidence: 96%
See 1 more Smart Citation